Study on the Quantitative Assessment of Impact Damage of Yellow Peaches Using the Combined Hyperspectral Technology and Mechanical Parameters - Feng Zhang; Bin Li; Hai Yin; Jiping Zou; Aiguo Ouyang (Journal of Spectroscopy)
The quantitative description of the impact damage of yellow peaches is an essential basis for evaluating their quality and guiding their postharvest handling. In this study, the combined hyperspectral technology and mechanical parameters method were used to quantitatively investigate the impact damage of yellow peaches. Firstly, the mechanical parameters, which are damaged area, absorbed energy, maximum contact force, and maximum stress of yellow peaches, were obtained by the impact device. The statistical regression models between mechanical parameters and damage area were established, and the results showed that the absorbed energy and maximum contact force are the optimal parameters to characterize the impact damage of yellow peaches. Then, the raw spectra were preprocessed by three spectral pretreatment methods, which are standard normal variate (SNV), multiplicative scatter correction (MSC), and SG smoothing, respectively, and the feature wavelengths were selected by the competitive adaptive reweighted sampling (CARS), and the quantitative relationships between spectra and mechanical parameters were successfully modeled based on partial least squares regression (PLSR). The results showed that there is a strong linear correlation between the spectral data and the mechanical parameters, and the prediction performance of the SNV-CARS-PLSR model is best, and the RP and RMSEP of the damaged area, absorbed energy, maximum contact force, and maximum stress of it were 0.920 and 86.452 mm2, 0.845 and 1.303 J, 0.943 and 49.666 N, 0.660 and 0.146 MPa, respectively. In a word, this study shows that the combined hyperspectral technology and mechanical parameters method can be used to quantitatively assess the impact damage of yellow peaches, and guide the postharvest handling of fruits.